Authority Curved Inward: A Psycho-Hermeneutical Reading of Narcissistic Leadership in Biblical Texts and Implications for Indonesian Ecclesial Discourse - Tri Astuti (Jurnal Ilmiah Tafsir Alkitab, 2026)
This article argues that narcissistic distortion in Christian religious leadership constitutes a theological deformation of authority, which this study designates as the inward curvature of authority, rather than a merely psychological or moral failure. Through a psycho-hermeneutical analysis of five biblical passages, namely Ezekiel 34:1-10, Matthew 23:1-12, 3 John 9-10, Mark 10:42-45, and John 13:1-17, the study attends to specific lexical and grammatical features: the reflexive use of ra'ah in Ezekiel, habitual present disjunctions in Matthew, the dispositional philoproteuon in 3 John, domination verbs in Mark, and the eidos-grounded service syntax in John 13. The analysis demonstrates that these texts together disclose a coherent scriptural grammar distinguishing distorted from restored authority. Three recurring features of distorted authority emerge across the corpus: self-referentiality, instrumentalization of others, and systematic resistance to reciprocity and correction. These textual findings are brought into critical dialogue with Indonesian ecclesial discourse, where leadership idioms such as gembala, hamba Tuhan, and bapa rohani have functioned to legitimate asymmetrical power structures. The study contributes a biblically grounded theological framework for pastoral discernment, leader formation, and ecclesial accountability in the Indonesian Christian context.